'Net' Social Change: Grassroots Empowerment for Sustainable Development - Dhakal, Subas P. (IGI Global, 2015)
The notion of empowerment broadly refers to the ability of actors to fulfil their missions. However, assessing Information and Communication Technology (ICT) specific contributions to this remains an exigent task in the context of grassroots organizations. The objective of this chapter is to analyse the differences in levels of empowerment between ICT adopters and non-adopters Grassroots Environmental Organizations (GEOs) in Perth, Western Australia. The chapter draws on organizational empowerment theory and proposes an evaluation framework to assess ICT-mediated empowerment for sustainable development. Utilizing a survey of GEOs and interviews with leaders, the chapter unravels the contributions of ICTs in enabling these grassroots actors. The chapter ends with the discussion on the need for overcoming digital divide and recommends strategic support for GEOs that are either not able to or not willing to keep up with the emerging trend of ICTs.